Learning Media of Physics-Based on Google Sites with QR Code on Particle Dynamics Material - Suci Prihatiningtyas; Muhammad Hilmi Arrofi’uddin; Novia Ayu Sekar Pertiwi (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2022)
The purpose of this research is to describe the feasibility of physics learning media and user responses when using Google Sites with QR codes as physics learning media on particle dynamics material. This research is research and development (R&D) using the Borg & Gall teaching model. The data collected in this research were in the form of student response data and media feasibility tests. Media feasibility sheets and student questionnaires as research instruments. Data analysis used descriptive qualitative and quantitative analysis. The results showed that the proportion of material experts and media experts for Google Sites-based physics learning media with QR codes on particle dynamics material was 88.9% with very good criteria. Overall, the user response rate was 88.9% after using Google Sites-based physics learning media with QR codes on particle dynamics material having very good criteria. From the results of this development study, it was concluded that the Google Sites-based physics learning media with a QR code on particle dynamics material met the requirements and criteria, was very useful, and was very good and feasible to be used as a physics learning tool for high school class X students.